PENERAPAN MEDIA PEMBELAJARAN E-BOOK CERITA RAKYAT DALAM PENINGKATAN KEMAMPUAN MEMBACA SISWA KELAS IV SD NEGERI 45 BIRING BALANG KECAMATAN PATTALASSANG KABUPATEN TAKALAR - Mifta Fausia Saharuddin; Karumpa, Aco; Rajab, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the process of implementing e-book folklore learning media in improving the reading ability of Grade IV students at UPT SD Negeri 45 Biring Balang, Pattallassang District, Takalar Regency. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of four stages: planning, acting, observing, and reflecting. The research subjects were 24 students. Data collection instruments included observation sheets and essay tests. Results showed significant improvement: the average reading test score increased from 68.96 (Cycle I) to 88.13 (Cycle II), and classical completeness increased from 54.17% to 100.00%. Therefore, the implementation of e-book folklore learning media is proven effective in improving students' reading ability.